Protein Misfolding and ER Stress in Huntington's Disease - Shacham, Talya; Sharma, Neeraj; Lederkremer, Gerardo Z. (Frontiers in Molecular Biosciences, 2019)
Increasing evidence in recent years indicates that protein misfolding and aggregation, leading to ER stress, are central factors of pathogenicity in neurodegenerative diseases. This is particularly true in Huntington’s disease (HD), where in contrast with other disorders, the cause is monogenic. Mutant huntingtin interferes with many cellular processes, but the fact that modulation of ER stress and of the unfolded response pathways reduces the toxicity, places these mechanisms at the core and gives hope for potential therapeutic approaches. There is currently no effective treatment for HD and it has a fatal outcome a few years after the start of symptoms of cognitive and motor impairment. Here we will discuss recent findings that shed light on the mechanisms of protein misfolding and aggregation that give origin to ER stress in neurodegenerative diseases, focusing on Huntington’s disease, on the cellular response and on how to use this knowledge for possible therapeutic strategies.